Workforce Diversity / Ummi Hanim Mohd Nazir ...[et al.] - Mohd Nazir, Ummi Hanim; Mohammad, Rohana; Kasim, Noorizma; Muhamed Muaidi, Nur Hidayah (2008)
Workforce diversity is the concept that organizations are becoming more heterogeneous in terms of gender, age, race, ethnicity, sexual orientation, and inclusion of other diverse groups